Exosomes Derived From M2 Macrophages Facilitate Osteogenesis and Reduce Adipogenesis of BMSCs - Li, Ziyi; Wang, Yafei; Li, Shilun; Li, Yukun (Frontiers in Endocrinology, 2021)
Bone regeneration is a complex process that requires the coordination of osteogenesis and osteoclastogenesis. The balance between osteogenesis and adipogenesis of bone marrow mesenchymal stem cells (BMSCs) plays a major role in the process of bone formation. Recently, intercellular communication between bone cells and surrounding cells has been gradually recognized, and macrophages on the surface of bone have been proven to regulate bone metabolism. However, the underlying mechanisms have not been fully elucidated. Recent studies have indicated that exosomes are vital messengers for cell-cell communication in various biological processes. In this experiment, we found that exosomes derived from M2 macrophages (M2D-Exos) could inhibit adipogenesis and promote osteogenesis of BMSCs. M2D-Exo intervention increased the expression of miR-690, IRS-1, and TAZ in BMSCs. Additionally, miR-690 knockdown in M2 macrophages with a miR-690 inhibitor partially counteracted the effect of M2D-Exos on BMSC differentiation and the upregulation of IRS-1 and TAZ expression. Taken together, the results of our study indicate that exosomes isolated from M2 macrophages could facilitate osteogenesis and reduce adipogenesis through the miR-690/IRS-1/TAZ axis and might be a therapeutic tool for bone loss diseases.